Image of the Golden Horde Tatar-Mongols and Ilkhans in the Writings of Crusade Propagandists (late 13th – early 14th centuries) » - Alexandar Nikolov (Золотоордынское обозрение, 2015)
By the end of the 13th century, when the Tatar-Mongols were already well-known in Latin Europe, several experts in the Near East affairs tried to specify the real place of the Tatars of the Golden Horde and the Ilkhan Horde in the complicated geopolitical complex, related to the struggle for the liberation of the Holy Land and the Holy Sepulchre from the “yoke of the Saracens”. The experts had to explain to the Western European elites how they should perceive the two Western uluses of the formerly united Mongol Empire of the Chinggisids. The relations with the Golden Horde and the Ilkhans of Iran appeared to be of crucial importance for the liberation and preservation of the Holy Land. Thus, two images of the Tatars took shape gradually: that of potential enemies in the case of the Golden Horde, and the possible allies in the case of the Ilkhans. This text is dedicated to several treatises of these propagandists, unified under the title and the slogan De Recuperatione Terrae Sanctae. The main focus is on the treatises of Hayton of Corycus (“Flower of the Histories of the Orient”) and of Marino Sanudo Torsello (“The Secrets of the Faithful to the Cross”), where we could find extremely interesting information on the Western European image of the Tatars. Several other excerpts are included in the text, namely passages from the treatises of William Adam (“How to exterminate the Saracens”), Pseudo-Brocardus (“A Guideline of Organization of a Crusade”) and the founder of this genre – Fidenzio di Padova (“A Book for the Recovery of the Holy Land”), where the political and military tendencies are defined very clear. The evolution of the image of the Tatar-Mongols developed from “children of the Tartar” to “bonnes sauvages” and “global rulers”, that are able to handle even the holy cause of the liberation of the Promised Land of the Christian people.